A review on flexion angle in high-flexion total knee arthroplasty for indonesian’s need - Darmanto, D.; Novriansyah, R.; Anggoro, P. W.; Ismail, R.; Jamari, J.; Bayuseno, A. P. (Frontiers in Mechanical Engineering, 2022)
Artificial Knee Joint (AKJ) proposed as an alternative treatment for damaged knee joints of humans is reviewed. The commercial application of AKJ to Total Knee Arthroplasty (TKA) can help patients to improve their normal daily activities. Here the high-flex type artificial knee joint (High-Flex AKJ) is typically designed for the patient's convenience on which the more fantastic range of motion can be adjusted for extreme activities such as Seiza and Muslim praying. However, the present AKJ High-Flex has not fulfilled the needs of Indonesians for religious movements with a flexion angle of 1500-1650. Therefore, this review aims to examine the flexion range of High-Flex AKJ in TKA proposed for the needs of Indonesians. This study is a narrative review, all studies published reviewed are related to the range of flexion angles on the use of products from many manufacturers and various types that have been used by patients, as well as the development of a CAD-based AKJ design. It was proposed in the present study that the flexion angle on High-Flex AKJ may be optimized by thickening the posterior femoral condyle, creating a medial pivot system, and applying a single radius system on the femoral component. Whereas, the tibial insert component could be designed by setting up the posterior tibial slope, and creating a post-cam stabilizer mechanism. Many knowledge gaps related to the population of research objects, lack of research on extreme angles, and development of AKJ components, are discussed. Further needs of extensive research on TKA in Mongoloid races are anticipated to be introduced for extreme angles and the most comprehensive product development for optimization of the flexion angle